Negative Selection Based Shadow Detection Algorithm - Firildak, Kazim; Karakose, Mehmet (Ieee, 2015)
Shadow regions are detected as objects at image segmentation, object detection and tracking applications. So, it affects negatively the accuracy and performance of algorithms. In this study, artificial immune system-based negative selection algorithm (YBSG) is proposed in order to determine shadow region. This algorithm obtains fast and effective solution to detect nonlinear change shadow region on the video scenes. This algorithm obtains us to increase in 5%-20% shadow detecting performance and 5%-10% execution time with effective method proposed to detect the shadows of different video scenes in literature.
Negatif Seçim Tabanli Gölge Tespit Algoritmasi
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: Shadow detection; Artifical immune system based shadow detection; Negative selection algorithm